Rancang Bangun Sistem Informasi Persediaan dan Permintaan Barang Proyek Kelistrikan Berbasis Web (Studi Kasus pada PT. Tea Kirana) - Ni Putu Widiani; Ni Made Estiyanti; I Putu Satwika (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2018)
The expansion of Information Technology (IT) is changing rapidly from time to time. Information Technology is holding the most important role in our lives nowadays. Information Technology is used in several fields, and in many corporations. The development of Information Technology is one of the most important parts of a company in order to increase the productivity of the company, be it in obtaining informations, processing and using the information on behalf of the company. PT. Tea Kirana is a construction company built on 1995 and is still operating today. The data supply of the company has been recorded and manged manually by the storage officer and the request of items has also been recorded manually on pieces of papers by the field supervisors. In this case, it takes a a long time to send the report to the management department and that is not efficient in order to establish a maximum report on time. Therefore the author has done an analysis and system design to overcome this problem in order to increase the efficiency in PT. Tea Kirana.